Strategies of Islamic Religious Education Teachers in Addressing Student Delinquency in Schools - Sari, Dina; Setiawan, Hasrian Rudi; Prasetia, Indra (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2025)
This study examines the strategies used by Islamic Religious Education (PAI) teachers to address student delinquency in junior high schools in Bandar Pasir Mandoge District, Asahan Regency. Using a qualitative approach with a multisite case study method, the research identifies delinquency types, causes, and intervention effectiveness. Findings reveal common issues such as truancy, improper mobile phone use, disrespect, avoidance of religious activities, and physical altercations. Contributing factors include weak religious foundations, economic struggles, lack of parental involvement, peer influence, and educational challenges. PAI teachers implement strategies like moral guidance, individualized mentoring, structured religious activities, parental collaboration, and rehabilitation programs. Schools with strong religious reinforcement programs show reduced misconduct, but inconsistent parental support and teacher workload remain obstacles. This study recommends standardized character education policies, enhanced teacher training, and greater parental engagement. The findings contribute to discussions on religious-based character education and student delinquency prevention in junior high schools.